2018
DOI: 10.1038/s41598-018-29092-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential of residual Pap test fluid as a resource for the metaproteomic analysis of the cervical-vaginal microbiome

Abstract: The human cervical-vaginal area contains proteins derived from microorganisms that may prevent or predispose women to gynecological conditions. The liquid Pap test fixative is an unexplored resource for analysis of microbial communities and the microbe-host interaction. Previously, we showed that the residual cell-free fixative from discarded Pap tests of healthy women could be used for mass spectrometry (MS) based proteomic identification of cervical-vaginal proteins. In this study, we reprocessed these MS ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Due to the important role of database in metaproteomic analysis, we compared two different databases to identify proteins in our dataset: (i) UniProt database restricted to human and microbial entries (73,910,451, release August 2017) and filtered using the MetaNovo pipeline [ 34 ] and (ii) vaginal metagenome-based database with human proteins obtained from the study of Afiuni-Zadeh et al [ 35 ]. The raw data were processed using MaxQuant version 1.5.7.4 against each database, separately.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the important role of database in metaproteomic analysis, we compared two different databases to identify proteins in our dataset: (i) UniProt database restricted to human and microbial entries (73,910,451, release August 2017) and filtered using the MetaNovo pipeline [ 34 ] and (ii) vaginal metagenome-based database with human proteins obtained from the study of Afiuni-Zadeh et al [ 35 ]. The raw data were processed using MaxQuant version 1.5.7.4 against each database, separately.…”
Section: Methodsmentioning
confidence: 99%
“…Proteomic studies have been performed on cervicovaginal fluid to analyze and understand the role of the microbiota on the cervical region metabolism [87][88][89]. A study using proteomic data showed that dysbiosis causes cervicovaginal inflammation and detrimental changes within the mucosal barrier [90].…”
Section: Cervicovaginal Microbiota and Relationship To Viral Infectionmentioning
confidence: 99%
“…A study using proteomic data showed that dysbiosis causes cervicovaginal inflammation and detrimental changes within the mucosal barrier [90]. Another recent study shows that cervicovaginal microbiome proteomic analysis may be conducted using the residual Papanicolaou test supernatants for community composition and functional microbiota characterization [87]. Proteomic analysis can be used in research to understand the cervicovaginal microbiome and its contribution to women's health and disease in the metabolic context.…”
Section: Cervicovaginal Microbiota and Relationship To Viral Infectionmentioning
confidence: 99%
“…Since common medium- or large-scale VM analyses employed this technique, the role of non-bacterial constituents of the VM in HPV infection and disease has not yet been described. Therefore, proteomic analysis could be key to a more complete understanding of the VM and its influence on disease in the metabolic context [ 142 , 143 ]. Only after the pathogenic mechanisms of interaction between microbiota and HPV have been fully understood will it be possible to identify the most effective therapeutic strategy.…”
Section: Future Prospectsmentioning
confidence: 99%